2018
DOI: 10.1016/j.avsg.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Assessment as a Predictor of Outcome in Older Vascular Surgery Patients

Abstract: Morphometric analysis predicts poorer outcome in a broad cohort of vascular surgery patients. Such assessment is likely to enhance patient counseling regarding individual risk as well as enhancing the ability to undertake risk-modified surgical audit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…on their comprehensive article, describing the influence of total psoas muscle area (TPMA) on mortality following elective abdominal aortic aneurysm (AAA) repair. We were struck by the similarity between the authors' findings and those of our own group. Similar to Waduud et al ., we found that TPMA is a poor indicator of mortality in general vascular surgery patients.…”
supporting
confidence: 65%
“…on their comprehensive article, describing the influence of total psoas muscle area (TPMA) on mortality following elective abdominal aortic aneurysm (AAA) repair. We were struck by the similarity between the authors' findings and those of our own group. Similar to Waduud et al ., we found that TPMA is a poor indicator of mortality in general vascular surgery patients.…”
supporting
confidence: 65%
“…The hypothesis of this study was that TPMA might therefore be a useful clinical adjunct for risk stratification in patients with an AAA. Associations between sarcopenia and adverse outcomes have been reported following elective AAA intervention. This finding was not, however, replicated by Heard and colleagues in a cohort of vascular patients in the UK.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, there were also reported variations in the vertebral level at which measurements were performed. The studies by Chowdhury et al . and Heard et al .…”
mentioning
confidence: 99%
“…It is important to note that the results of previous studies must be interpreted with caution. First, it remains unclear whether any of these were adequately powered to detect the stated outcome measures.…”
mentioning
confidence: 99%
See 1 more Smart Citation